Computational and Statistical Issues in Personalized Medicine - Lippert, Christoph; Heckerman, David (XRDS: Crossroads, The ACM Magazine for Students - Computational Biology, 2015)
Computational methods can be used to find associations between our genome and our traits, and new optimizations to these computations promise to do it much faster.